Pengaruh Media Instagram Terhadap Pemasaran Produk Sate Bandeng Ibu Amenah di Kota Serang - Sundaya, Arsyan Hashfi; Budiawati, Yeni; Sariyoga, Setiawan (Universitas Wiralodra, 2025)
This study analyzes the influence of Instagram as a marketing medium on Sate Bandeng products, focusing on UMKM Sate Bandeng Ibu Amenah in Serang City. Using a quantitative descriptive approach with 92 respondents, data were collected through questionnaires, interviews, and documentation, and analyzed using multiple linear regression with the EPIC model (Empathy, Persuasion, Impact, Communication). The results show that only the Empathy variable has a significant effect on sales, while Persuasion, Impact, and Communication do not significantly influence purchasing decisions. These findings highlight that emotional closeness built through empathetic content such as storytelling, testimonials, and cultural values is the key factor in increasing consumer engagement and sales, proving Instagram’s effectiveness as a marketing tool for SMEs.